Analisis Pelaksanaan Pengelolaan Sampah di Kabupaten Aceh Barat - Yulianita Yulianita; Mursyidin Mursyidin; Wardah Muharriyanti Siregar (Journal of Social and Policy Issues, 2021)
The ratification of West Aceh District Regulation (Qanun) Number 4 of 2017 concerning waste management has become a guideline for the West Aceh District government to achieve solid waste management objectives. The regional regulation guarantees legal certainty, clarity of responsibility of the authority of the regional government, the participation of the community and the business sector / private sector so that waste management can run effectively and efficiently. The purpose of this study was to determine the implementation of Qanun Number 4 of 2017 Article 10 concerning waste management in West Aceh Regency in 2019. The method used in this study was to use a qualitative descriptive approach. Data collection techniques used are documentation and interviews. The informants in this study were 8 people. Data analysis was performed using qualitative data analysis techniques. The results showed that the implementation of Qanun Number 4 of 2017 Article 10 concerning waste management in West Aceh District Year 2019 in waste reduction was still not optimal, this was due to the lack of effort and management of the government in managing waste in the community environment such as lack of facilities and infrastructure in management garbage. There are still many piles of rubbish on the edges of the highway that make West Aceh District still look dirty and dirty. For the handling of waste carried out by the Office of Environment of West Aceh District Head is not optimal, this is because the lack of cleaners is also a major factor in the failure of waste management. There has been no firm action from the government on waste management efforts such as the implementation of West Aceh District Qanun Number 4 of 2017 Chapter XVII on Article 63 Criminal Provisions and lack of socialization from the government on waste management so that public awareness in managing waste is still reduced